(untitled) - Ghysels, Eric (New York, 2001)
Economic and financial time series feature important seasonal fluctuations. Despite their regular and predictable patterns over the year, month or week, they pose many challenges to economists and econometricians. This book provides a thorough review of the recent developments in the econometric analysis of seasonal time series. It is designed for an audience of specialists in economic time series analysis and advanced graduate students. It is the most comprehensive and balanced treatment of the subject since the mid-1980s.
Keywords: Econometrics,Time-series analysis; Toán kinh tế,Phân tích chuỗi thời gian